2009
DOI: 10.1099/vir.0.006833-0
|View full text |Cite
|
Sign up to set email alerts
|

Alpha interferon as an adenovirus-vectored vaccine adjuvant and antiviral in Venezuelan equine encephalitis virus infection

Abstract: There are no widely available vaccines or antiviral drugs capable of protecting against infection with Venezuelan equine encephalitis virus (VEEV), although an adenovirus vector expressing VEEV structural proteins protects mice from challenge with VEEV and is potentially a vaccine suitable for human use. This work examines whether alpha interferon (IFN-α) could act as an adjuvant for the adenovirus-based vaccine. IFN-α was either expressed by a plasmid linked to the adenovirus vaccine or encoded by a separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…However, if given on day 3 postinfection, there was no significant effect on the levels of virus recovered from the feet or any effect on disease. This parallels other previous reports that showed that IFN-␣ treatment is less effective against alphaviral encephalitic disease when given later in infection (21,53). The activation of suppressors of cytokine signaling proteins by the inflammatory response (11) and/or disruption of IFN-␣/␤ signaling by viral proteins (64) may be involved in limiting the effectiveness of IFN-␣ treatment in an established infection.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, if given on day 3 postinfection, there was no significant effect on the levels of virus recovered from the feet or any effect on disease. This parallels other previous reports that showed that IFN-␣ treatment is less effective against alphaviral encephalitic disease when given later in infection (21,53). The activation of suppressors of cytokine signaling proteins by the inflammatory response (11) and/or disruption of IFN-␣/␤ signaling by viral proteins (64) may be involved in limiting the effectiveness of IFN-␣ treatment in an established infection.…”
Section: Discussionsupporting
confidence: 88%
“…The significantly higher levels of IFN-␣/␤ induced by the Reunion Island isolate on day 2 than those induced by the Asian isolate (Fig. 5A) were not associated with lower viremia, as might be expected (53,60), but did correlate with lower Reunion Island virus titers in the feet on that day (Fig. 1D).…”
Section: Chikv Infection Was Associated With Induction Of Tnf-␣ Mcp-supporting
confidence: 55%
“…challenge with western equine encephalitis virus (WEEV) at 24 h after DEF201 treatment (37). Similar results were also seen in a mouse model of Venezuelan equine encephalitis virus (VEEV) infection, with 24 h pretreatment protecting against a lethal challenge (29). In addition, it has been demonstrated that the murine form of DEF201 has efficacy in a mouse model of severe acute respiratory syndrome coronavirus (SARS-CoV), as DEF201 provided complete survival benefit up to 14 days prior to lethal challenge (19).…”
Section: Discussionsupporting
confidence: 55%
“…Treatment at 6 h after virus challenge in a mouse model of WEEV infection resulted in significantly improved survival (37). While efficacy after prophylactic treatment was demonstrated in a model of VEEV infection, therapeutic efficacy was not observed with Ad5-vectored mouse IFN, where delay of treatment to 6 h after virus challenge did not protect mice from death (29). Finally, it has been demonstrated that the murine form of DEF201 has significant treatment efficacy in a lethal mouse model of SARS-CoV at 6 h and 12 h postinfection (19).…”
Section: Discussionmentioning
confidence: 98%
“…IFN-α has successfully been shown to improve the protective immunity of peptide and vector-based vaccines in experimental models. When type I IFNs were used an adjuvant in clinical trials in patients with cancers, both immunological and clinical responses were observed 36,44 . In addition, interleukin -2 and -12 (IL-2 and IL-12) have also been used as adjuvants in cancer therapy, as both cytokines are potent stimulators for cytotoxicity of CD8 T cells.…”
Section: 0 Vaccines and Adjuvantsmentioning
confidence: 99%